2020
DOI: 10.3390/ijerph17134616
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Socioeconomic Status and Air Pollution Levels on the Public Perception of Local Air Quality in a Mexico-US Border City

Abstract: Air pollution in developing countries is a growing concern. It is associated with urbanization and social and economic structures. The understanding of how social factors can influence the perception and the potential impact of air pollution have not been addressed sufficiently. This paper addresses the social vulnerability and exposure to PM10 association and its influence on the air quality perception of residents in Mexicali, a Mexico–US border city. This study used individual variables and populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
0
10
0
3
Order By: Relevance
“…Studies conducted in China have similarly reported a correlation between awareness of air pollution and the age variable (20). However, another study has suggested that the age variable is not a significant factor in perceived air pollution (21). The discrepancies in findings across studies regarding the age variable's impact on the perception of air pollution may be attributed to variations in pollution levels in the regions where the studies were conducted.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies conducted in China have similarly reported a correlation between awareness of air pollution and the age variable (20). However, another study has suggested that the age variable is not a significant factor in perceived air pollution (21). The discrepancies in findings across studies regarding the age variable's impact on the perception of air pollution may be attributed to variations in pollution levels in the regions where the studies were conducted.…”
Section: Discussionmentioning
confidence: 96%
“…However, due to the Logistic Regression analysis, this relationship disappeared. In addition, the studies found a difference between the level of education in the literature and the level of knowledge about air pollution (21,22). Some studies have determined that the perception of environmental risk, including air pollution increases as the class level increases (19,23).…”
Section: Discussionmentioning
confidence: 99%
“…(3) It illustrates the disparity in the number of positive cases found in men and women in Pakistan. (4) The typhoid module provides reliable predictions of positive cases in many places. In the end, it pinpointed the locations that were most severely affected.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, children are victims of waterborne diseases due to poor hygienic water and weak immunity, especially since the condition is more aggravated in developing countries, including Pakistan. According to an estimate, 230,000 children die annually in Pakistan because of waterborne diseases [ 4 ]. According to the State Bank of Pakistan's report on health, included in the Sindh Vision 2030, water-related environmental health concerns impose the greatest health burden.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic factors such as income, education, and job have been shown to have a direct correlation with health, regarding indoor air quality (Laurent et al, 2007). Socioeconomic factors can influence air quality due to the proximity to vehicle exhaust (Aung et al, 2018), dilapidated structures (Bernard et al, 2007), and inferior building materials (Muñoz-Pizza et al, 2020).…”
Section: Socioeconomic Status and Social Injusticementioning
confidence: 99%